Ultrafast all-optical control of the magnetization in magnetic dielectrics - Kirilyuk, Andrei; Kimel, Alexey; Hansteen, Fredrik; Pisarev, Roman V.; Rasing, Theo (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The purpose of this review is to summarize the recent progress on laser-induced magnetizationdynamics in magnetic dielectrics. Due to the slow phonon–magnon interaction in these materials, direct thermal effects of the laser excitation can only be seen on the time scale of almost a nanosecondand thus are clearly distinguished from the ultrafast nonthermal effects. However, via the crystal field, laser pulses are shown to indirectly modify the magnetic anisotropy in rare-earth orthoferrites and lead to the spin reorientation within a few picoseconds. More interesting, however, are the direct nonthermal effects of light on spin systems. We demonstrate coherent optical control of the magnetization in ferrimagnetic garnet films on a femtosecond time scale through acombination of two different ultrafast and nonthermal photomagnetic effects and by employing multiple pump pulses. Linearly polarized laser pulses are shown to create a long-lived modification of the magnetocrystalline anisotropy via optically induced electron transfer between nonequivalent ion sites. In addition, circularly polarized pulses are shown to act as strong transient magnetic field pulses originating from the nonabsorptive inverse Faraday effect. An all-optical scheme of excitation and detection of different antiferromagnetic resonance modes with frequencies of up to 500 GHz will be discussed as well. The reported effects open new and exciting possibilities for ultrafast manipulation of spins by light, and provide new insight into the physics of magnetism on ultrafast time scales.